Multivariate analysis in the characterization of feijoa fruits (Acca sellowiana [O. Berg] Burret) in Tungurahua, Ecuador - Palacios-Villacrés, Augusto; Sánchez-Mora, Fernando; Onofre , Rubens (Revista de la Facultad de Agronomía de la Universidad del Zulia, 2025)
The feijoa (Acca sellowiana [O. Berg] Burret) is a Myrtaceae native to southern Brazil and northern Uruguay. Its fruits can be consumed fresh or processed into juice, ice cream, wine, liqueurs and others. In Ecuador, feijoa cultivation has been reported since 1980 in the province of Tungurahua. To evaluate the morphological and physicochemical characteristics of feijoa fruits through multivariate analysis, fruits from 18 farms located in Tungurahua, Ecuador were analyzed. A sample of 10 fruits per farm were analyzed in the food processing laboratory of the Tungurahua Higher Technological Institute. Descriptive statistics and multivariate analysis were employed for data evaluation. The fruits exhibited an oboval shape with erect sepals, moderate skin roughness, and white pulp. Fruit diameter ranged from 2.0 to 5.1 cm (CV=17 %), and fruit length ranged from 2.46 to 10.1 cm (CV=16.2 %), indicating variability in fruit size. Fruit biomass ranged from 8 to 133 g, with pulp yields between 4.6 % and 46.2 %. Total soluble solids ranged from 8.0 to 20 °Brix; the pH and titratable acidity (citric acid percentege) averaged 3.5 and 0.50, respectively. Fruit length and diameter showed a high correlation with fruit biomass. PCA identified the formation of three groups of producers, based on fruit size